Uji Kelayakan Kandungan Unsur Air Tanah Daerah Terdampak Lapindo Kecamatan Porong Menggunakan XRF - Mauliana, Metatia Intan; Suprayitno, Eko Agus (Universitas Negeri Yogyakarta, 2017)
The existence of hot mud Lapindo has an impact on threatened ecosystems, economic downturn, and the destruction of educational facilities and transportation. In addition, according to a study in 2013 found that the information content of metals in samples Lumpur Lapindo that harmful to the body if consumed. This research done to determine whether the content of the Lapindo mud is impacting on element content of groundwater in the affected areas, especially at Glagah arum and Gedang are located in the district Porong. The test used X-ray Fluorescence (XRF) spectrometry to determine the elements on ground water sources, as well as pH testing and Total Dissolve Solid (TDS) as data pendukung of XRF result and to obtain another character of ground water. The method used in the sampling is random sampling method as much as four samples, two samples in the village of Glagah Arum (1A and 1B), and 2 samples in the village of Gedang (2A and 2B). Based on the XRF results obtained that the content of metallic elements found only in one sample were at Gedang area is Pb 25.08 m/m%, U 16.08 m/m%, Px 8.04 m/m%, Nb 7.60 m/m%, dan In 7.47 m/m% . Then result of the fourth pH samples are 8:31, 8:23, 6.99, and 8:45. While the results of TDS are 0.88 mg / L, 0:18, 0:52 mg / L, and 0.83 mg/L by gravimetric method. Overall results of the testing parameters of four samples showed that samples taken in the village Glagah Arum and Gedang did not indicate any danger if used in everyday use but not for consumption so it is not necessary to follow-up such as socialization.